Valery Gergiev conducts Prokofiev - Daniil Trifonov performs the 1st Piano Concerto Symphony Orchestra of the Mariinsky Theater - The complete Prokofiev symphonies. Moscow Easter Festival - Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953 (Idéale Audience, 2012)
Valery Gergiev opened the Moscow Easter Festival in April 2012 with the Mariinsky Theatre Orchestra and the young pianist Daniil Trifonov, his first appearance on medici.tv. Mentored by musicians including Gergiev and Martha Argerich, Trifonov had exploded onto the international scene in 2010 and 2011: after being awarded Third prize at the Chopin International Piano Competition in Warsaw, he won First prize at the Rubinstein Competition in Tel Aviv and the Grand Prix at the Tchaikovsky Competition in Moscow. In this concert, he performs Prokofiev's First Piano Concerto. Gergiev opens and closes the concert with the composer's two most popular symphonies: the First Symphony, written in the mid-1910s, and the Fifth Symphony (1944-45). The Moscow Easter Festival is held annually, starting on Easter Sunday (according to the historical Julian calendar). The 2012 festival was dedicated to the music of Sergei Prokofiev. The Mariinsky Orchestra, which has been led by Gergiev for over 20-years, has a unparalleled reputation in Russian repertoire, performing the composer's symphonies, concertos and operas regularly around the world. This concert was broadcast live on medici.tv
Keywords: Symphonies; Concertos (Piano); Concertos; Concert films; Internet videos